Given that are complex numbers satisfying the system of equations Find the total number of positive integers such that is an integer.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
From Newton's Identities we have:
p k = x k + y k + z k
e 1 = x + y + z
e 2 = x y + y z + x z
e 3 = x y z
For this case:
p 1 = 1
p 2 = 2
p 3 = 3
Calculating e 1 , e 2 and e 3
Since e 1 = p 1 :
e 1 = 1
For e 2 :
p 1 2 = 1 = x 2 + y 2 + z 2 + 2 ( x y + y z + x z ) = 2 + 2 e 2
e 2 = − 2 1
And for e 3 :
p 1 e 2 = − 2 1 = x y 2 + x 2 y + x z 2 + x 2 z + y z 2 + y 2 z + 3 x y z
p 1 e 2 = − 2 1 = x y 2 + x 2 y + x z 2 + x 2 z + y z 2 + y 2 z + 3 e 3
x y 2 + x 2 y + x z 2 + x 2 z + y z 2 + y 2 z = − 2 1 − 3 e 3
p 1 3 = 1 = x 3 + y 3 + z 3 + 3 ( x y 2 + x 2 y + x z 2 + x 2 z + y z 2 + y 2 z ) + 6 x y z
p 1 3 = 1 = 3 + 3 ( − 2 1 − 3 e 3 ) + 6 e 3
e 3 = 6 1
Again from Newton's identities, for k > 3 , we'll have:
p n = i = n − 3 ∑ n − 1 ( − 1 ) n − 1 + i e n − i p i
p n = ( − 1 ) 2 n − 4 p n − 3 e 3 + ( − 1 ) 2 n − 3 p n − 2 e 2 + ( − 1 ) 2 n − 2 p n − 1 e 1
p n = 6 1 p n − 1 + 2 1 p n − 2 + p n − 3
6 p n = p n − 1 + 3 p n − 2 + 6 p n − 3
From this point on, we have to check whether p n − 1 + 3 p n − 2 + 6 p n − 3 produces a multiple of 6 , for p n to be an integer. Calculating the first items:
p 4 = 6 2 5
p 5 = 6
p 6 = 1 2 1 0 3
p 7 = 1 8 2 2 1
p 8 = 7 2 1 2 6 5
From this point on each factor for 6 p n in the aforementioned formula will always have non-integer 6 p n − 3 , since the denominator of p n − 3 will always be greater than 6 . So, 6 p n will never be an integer and, of course, will never be a multiple of 6 .
So it only occurs at n = 5 . The answer is, then, 1